2020
DOI: 10.1183/23120541.00541-2020
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of COVID-19 patients treated with continuous positive airway pressure outside the intensive care unit

Abstract: AimWe aim at characterising a large population of Coronavirus 19 (COVID-19) patients with moderate-to-severe hypoxemic acute respiratory failure (ARF) receiving CPAP outside intensive care unit (ICU), and ascertaining whether the duration of CPAP application increased the risk of mortality for patients requiring intubation.MethodsIn this retrospective, multicentre cohort study, we included COVID-19 adult patients, treated with CPAP outside ICU for hypoxemic ARF from March 1st to April 15th, 2020. We collected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
63
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(77 citation statements)
references
References 27 publications
11
63
1
1
Order By: Relevance
“…As previously described, 6 CPAP was delivered through helmets (Intersurgical, Mirandola (MO), Italy; Dimar, Medolla, MO, Italy) through flowmeter (60−70 L/min) and face masks (Intersurgical, Mirandola, MO, Italy; Dimar, Medolla, MO, Italy; Fisher&Paykel, Auckland, New Zealand; ResMed, San Diego, CA, USA; Philips Respironics, Murrysville, PA, USA) via flowmeters or Boussignac systems (typically 30−70 L/min). FiO 2 was set by regulating oxygen and air flow.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…As previously described, 6 CPAP was delivered through helmets (Intersurgical, Mirandola (MO), Italy; Dimar, Medolla, MO, Italy) through flowmeter (60−70 L/min) and face masks (Intersurgical, Mirandola, MO, Italy; Dimar, Medolla, MO, Italy; Fisher&Paykel, Auckland, New Zealand; ResMed, San Diego, CA, USA; Philips Respironics, Murrysville, PA, USA) via flowmeters or Boussignac systems (typically 30−70 L/min). FiO 2 was set by regulating oxygen and air flow.…”
Section: Methodsmentioning
confidence: 99%
“…As previously described, 6 respiratory intermediate care units were organized as follows. The nurse-to-patient ratio varied from a maximum of 1:6 both during day and night to a minimum of 1:8 and 1:12 during day and night, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…There was no difference in time from hospitalisation to initiation of CPAP/HFNO between survivors and non-survivors (median time to initiation [range] 2 days [1-30] vs 2 days [1][2][3][4][5][6][7][8][9][10][11][12][13][14]). The median duration of CPAP/HFNO treatment for all patients was 3.5 days (range 1 -24); there was no difference between survivors and non-survivors (median [range] = 4 [1-24] days vs. 3.5 [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] days, p=0.454).…”
Section: Survivors Vs Non-survivorsmentioning
confidence: 99%
“…The role of these non-invasive therapies has been examined in previous studies (2)(3)(4)(5) with variation in the reported outcomes. Predominantly these report outcomes from inside intensive care units, however, there is also data from patients treated outside of this setting (6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%